Mammalian SWI/SNF Chromatin Remodeling Complexes: Emerging Mechanisms and Therapeutic Strategies. Issue 12 (December 2020) - Centore, Richard C.; Sandoval, Gabriel J.; Soares, Luis Miguel Mendes; Kadoch, Cigall; Chan, Ho Man
Abstract : Small molecule-based targeting of chromatin regulatory factors has emerged as a promising therapeutic strategy in recent years. The development and ongoing clinical evaluation of novel agents targeting a range of chromatin regulatory processes, including DNA or histone modifiers, histone readers, and chromatin regulatory protein complexes, has inspired the field to identify and act upon the full compendium of therapeutic opportunities. Emerging studies highlight the frequent involvement of altered mammalian Switch/Sucrose-Nonfermentable (mSWI/SNF) chromatin-remodeling complexes (also called BAF complexes) in both human cancer and neurological disorders, suggesting new mechanisms and accompanying routes toward therapeutic intervention. Here, we review current approaches for direct targeting of mSWI/SNF complex structure and function and discuss settings in which aberrant mSWI/SNF biology is implicated in oncology and other diseases. Highlights: Over 20% of human cancers carry a mutation in mSWI/SNF complex subunit genes. Mistargeting of mSWI/SNF activity by disease-relevant transcription factors contributes to oncogenic gene expression programs. Targetable synthetic lethal opportunities exist for cancers harboring perturbations in mSWI/SNF subunits. The presence of alternate mSWI/SNF complex subtypes and variants enables complex-specific pharmacological targeting. Discovery and development of novel, subunit-specific small-molecule inhibitors and degraders are ongoing.